Myristoylated preS1-domain of the hepatitis B virus L-protein mediates specific binding to differentiated hepatocytes - Meier, Anja; Mehrle, Stefan; Mier, Walter; Urban, Stephan (Hepatology, 2013)
Chronic infection with the human hepatitis B virus (HBV) is a global health problem and a main cause of progressive liver diseases. HBV exhibits a narrow host range, replicating primarily in hepatocytes. Both host and hepatocyte specificity presumably involve specific receptor interactions on the target cell; however, direct evidence for this hypothesis is missing. Following the observation that HBV entry is specifically blocked by L-protein-derived preS1-lipopeptides, we visualized specific HBV receptor/ligand complexes on hepatic cells and quantified the turnover kinetics. Using fluorescein isothiocyanate-labeled, myristoylated HBV preS1-peptides we demonstrate (1) the presence of a highly specific HBV receptor on the plasma membrane of HBV-susceptible primary human and tupaia hepatocytes and HepaRG cells but also on hepatocytes from the nonsusceptible species mouse, rat, rabbit and dog; (2) the requirement of a differentiated state of the hepatocyte for specific preS1-binding; (3) the lack of detectable amounts of the receptor on HepG2 and HuH7 cells; (4) a slow receptor turnover at the hepatocyte membrane; and (5) an association of the receptor with actin microfilaments. The presence of the preS1-receptor in primary hepatocytes from some non-HBV-susceptible species indicates that the lack of susceptibility of these cells is owed to a postbinding step. Conclusion: These findings suggest that HBV hepatotropism is mediated by the highly selective expression of a yet unknown receptor* on differentiated hepatocytes, while species specificity of the HBV infection requires selective downstream events, e.g., the presence of host dependency or the absence of host restriction factors. The criteria defined here will allow narrowing down reasonable receptor candidates and provide a binding assay for HBV-receptor expression screens in hepatic cells. (HEPATOLOGY 2013)